2020
DOI: 10.7717/peerj.8663
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of osteogenic differentiation and mitochondrial function change in human periodontal ligament stem cells by melatonin at physiological levels

Abstract: N-Acetyl-5-methoxytryptamine (melatonin, MT) at pharmacological concentrations promotes the osteogenic differentiation of human bone marrow-derived mesenchymal stem cells; however, its role at physiological concentrations (1 pM–10 nM) remains unclear. We explored the effects of 1 pM–1 µM MT on the osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs) and its underlying mitochondrial dynamics-mediated mechanisms. T he PDLSC phenotype was detected by flow cytometry and evaluated for three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…Nevertheless, some experiments have produced conflicting results. In contrast to previous findings, one study reported that physiological melatonin concentrations (1 pM–10 nM) inhibited the osteogenic differentiation of human periodontal ligament stromal cells, while 1 μM melatonin (the lowest pharmacological concentration) promoted it ( Zheng et al, 2020 ). The acute melatonin treatment was also more effective than chronic exposure, which may be due to the desensitization of the melatonin receptors ( Radio et al, 2006 ).…”
Section: Melatonin Mediates Msc Osteogenesis Chondrogenesis and Adipogenesiscontrasting
confidence: 84%
“…Nevertheless, some experiments have produced conflicting results. In contrast to previous findings, one study reported that physiological melatonin concentrations (1 pM–10 nM) inhibited the osteogenic differentiation of human periodontal ligament stromal cells, while 1 μM melatonin (the lowest pharmacological concentration) promoted it ( Zheng et al, 2020 ). The acute melatonin treatment was also more effective than chronic exposure, which may be due to the desensitization of the melatonin receptors ( Radio et al, 2006 ).…”
Section: Melatonin Mediates Msc Osteogenesis Chondrogenesis and Adipogenesiscontrasting
confidence: 84%
“…We found that PEMF therapy had a positive effect on the expression of OPN, which is similar to the findings of Yin et al [2018]; however, MEL seemed to have no effect on the expression of this gene. Recently, Zheng et al [2020] demonstrated that the OPN expression level in human periodontal ligament stem cells (hPDLSCs) was downregulated by physiological MEL concentrations (1 pM-10 nM) and upregulated by the lowest pharmacological concentration (1 µM). Moreover, in a study on the mandibular distraction osteogenesis in rats, Acikan et al [2018] found that the OPN level was higher in the MEL groups with dosages of 25 and 50 mg/kg than in the control group, and the 50 mg/kg dose group had higher OPN levels than the 25 mg/kg dose group (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…According to the pre‐experiments, we observed that RNA and protein level reached the peak at the 8th day after osteogenic induction and melatonin treatment. Consequently, we conducted the measurement of osteogenesis and subsequent mitochondrial function tests, which is consistent with most previous literature on the osteogenesis of periodontal ligament cells 14,52,53 …”
Section: Discussionmentioning
confidence: 57%
“…Park et al also confirmed that melatonin promoted osteoblastic differentiation through the BMP/ERK/Wnt signaling pathways 50 . However, our previous research revealed that physiological concentrations of melatonin (10 nM, 100 pM, and 1 pM) had suppressed osteogenesis of hPDLSCs 14 . A possible explanation could be that regulating effect of melatonin is concentration‐dependent, Qiu et al 51 reported that melatonin inhibited the proliferation, differentiation, and apoptosis of osteoblasts in a concentration‐dependent manner.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation